PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN MEMBELI MOBIL MEREK TOYOTA AGYA DI KOTA PALU (PT. HADJI KALLA) - ARDIANSYAH, RIZCKY (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2016)
The objective of the research is to find out and analyze the influence of product quality on decision-making, both simultaneously and partially. The research is verificative. The sample involves consumers of Agya car at PT. Hadji Kalla. The analysis tool used is multiple linear regression analysis. The result of regression equation from the study is -2.887 + 0,237 X1+ 0,220X2 + 0,217X3 + 0,319X4 + 0,166X5 + 0,418X6 + 0,140X7. Product Quality partially has significant to decision-making.